Aeroservoelasticity Modeling and Control - Tewari, Ashish (Springer, 2015)
This book presents aeroservoelasticity (ASE) as a well-formed discipline with a systematic framework. While many research articles have appeared on the special applications of ASE–such as active flutter suppression and gust load alleviation– there are no textbooks and monographs on the general and systematic procedure to be followed in the modeling and analysis of aeroservoelastic systems. This book is a first step in trying to fill this important gap in the aerospace engineering literature. This book introduces the basic math modeling concepts and highlights important developments involved in structural dynamics, unsteady aerodynamics, and con trol systems. It also attempts to evolve a generic procedure to be applied for ASE system synthesis. The treatment includes finite-element structural modeling and de tailed unsteady aerodynamic modeling at various speeds for deriving the necessary aeroelastic plants, with sample control applications to active flutter suppression, load alleviation, and adverse ASE coupling...